Human bone marrow stem/stromal cell osteogenesis is regulated via mechanically activated osteocyte‐derived extracellular vesicles. (16th July 2020) - Eichholz, Kian F.; Woods, Ian; Riffault, Mathieu; Johnson, Gillian P.; Corrigan, Michele; Lowry, Michelle C.; Shen, Nian; Labour, Marie‐Noelle; Wynne, Kieran; O'Driscoll, Lorraine; Hoey, David A.
Abstract: Bone formation or regeneration requires the recruitment, proliferation, and osteogenic differentiation of stem/stromal progenitor cells. A potent stimulus driving this process is mechanical loading. Osteocytes are mechanosensitive cells that play fundamental roles in coordinating loading‐induced bone formation via the secretion of paracrine factors. However, the exact mechanisms by which osteocytes relay mechanical signals to these progenitor cells are poorly understood. Therefore, this study aimed to demonstrate the potency of the mechanically stimulated osteocyte secretome in driving human bone marrow stem/stromal cell (hMSC) recruitment and differentiation, and characterize the secretome to identify potential factors regulating stem cell behavior and bone mechanobiology. We demonstrate that osteocytes subjected to fluid shear secrete a distinct collection of factors that significantly enhance hMSC recruitment and osteogenesis and demonstrate the key role of extracellular vesicles (EVs) in driving these effects. This demonstrates the pro‐osteogenic potential of osteocyte‐derived mechanically activated extracellular vesicles, which have great potential as a cell‐free therapy to enhance bone regeneration and repair in diseases such as osteoporosis. Abstract : Bone formation/regeneration requires the recruitment and osteogenic differentiation of stem/stromal progenitor cells. A potent stimulus driving this process is mechanical loading. In his study, we demonstrate that osteocytes coordinate stem cell behavior in response to loading via modulation of their secretome that is delivered via extracellular vesicles (EVs). This therefore highlights mechanically activated EVs as potential therapies for bone regeneration.